Species and Functional Diversity of Deep-Sea Nematodes in a High Energy Submarine Canyon - Liao, Jian-Xiang; Wei, Chih-Lin; Yasuhara, Moriaki (Frontiers in Marine Science, 2020)
Gaoping Submarine Canyon (GPSC) off southwestern Taiwan is a high energy canyon connected to a small mountain river with extremely high sediment load (~10 kt km-2 y-1). Due to heavy seasonal precipitation (>3000 mm y-1) and high tectonic activity in the region, the GPSC is known for active sediment transport processes and associated submarine geohazards (e.g., submarine cable breaks). More importantly, strong internal tides have been recorded in the GPSC to drive head-ward, bottom-intensified currents, which result in sediment erosion and resuspension in response to the tidal cycles. To understand the effects of extreme physical conditions on marine nematodes, we sampled the surface sediments along the thalweg of upper GPSC and adjacent slope (200-1100 m) using a multicorer in the summer and fall of 2015. We found that the nematode species, functional, trophic diversity and maturity dropped significantly in the GPSC as compared with slope communities, but the nematode abundances were not affected by the adverse conditions in the canyon. The non-selective deposit-feeding, fast colonizing nematodes (e.g., Sabatieria, Daptonema, Axonolaimus, and Metadesmolaimus) dominated the canyon seafloor. In contrast, other species of non-selective deposit feeders (Setosabatieria and Elzalia), epigrowth feeders (Craspodema), omnivores/predators (Paramesacanthion), and other species constituted the diverse nematode assemblages on the slope. We found that the strong bottom currents in the GPSC may depress the local nematode diversity by removing the organic-rich, fine-grained sediments; therefore, only the resilient or fast recovering nematode species could survive and prevail. The high species turnover with depth and between the canyon and slope habitats demonstrates that strong environmental filtering processes were the primary mechanism shaping the nematode community assembly off SW Taiwan. Between the canyon and slope, a considerable contribution of nestedness pattern also indicates some degree of local extinction and dispersal limitation in the dynamic GPSC.